Enantiomeric separation of novel anticancer agent 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one - Shinde, Popat D.; Jadhav, Vinod H.; Borate, Hanumant B.; Bhide, Sunil R.; Sonawane, Kiran B.; Wakharkar, Radhika D. (Journal of Chromatography A, 2007)
The enantiomers of 5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2-en- 1-one, a novel anticancer agent, were separated by derivatisation with caronaldehyde, separation of the resulting diastereoisomers of the corresponding esters by silica gel column chromatography and regeneration of alcohols (S)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-one and (R)5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2- en- 1-one under aqueous conditions. The absolute configuration of the enantiomers was determined by H-1 NMR studies of the corresponding Mosher esters. Alternatively, the enantiomers were separated by preparative HPLC to collect the (S)- and (R)-5-hydroxy-3-(4-methoxyphenyl)-2-(3,4,5-trimethoxyphenyl)-cyclopent-2 -en-1-ones with high purity which was comparable with that obtained by the chemical method. The details of these methods have been presented herein. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Anticancer; column chromatography; diaryl cyclopentenone; diastereoisomers; enantioseparation; HPLC; Resolution